Relapse and temporomandibular joint dysfunction (TMD) as postoperative complication in skeletal class III patients undergoing bimaxillary orthognathic surgery: A systematic review - Neeraj; Srinivas Gosla Reddy; Ashutosh Dixit; Padmanidhi Agarwal; Rebecca Chowdhry; Ashi Chug (Journal of Oral Biology and Craniofacial Research)
Objectives: The aim of this study was to determine Relapse and TMD as postoperative complication in skeletal class III patients undergoing bimaxillary orthognathic surgery. Materials and methods: Data was obtained by database searching using The Cochrane Central Register of Controlled Trials (central), PUBMED, SCOPUS, EMBASE, Google scholar, National Medical library, New Delhi. The titles and abstracts of the electronic search results were screened and evaluated by two observers for eligibility according to the inclusion and exclusion criteria. Results: 5261 articles were retrieved for the review. Among these, 3474 duplicate articles were removed. 418 studies were selected based on the eligibility criteria. For the present review, 30 articles were included after elimination according to the inclusion criteria. The Prisma diagram flowchart demonstrates our selection scheme. Quality assessment criteria to evaluate the studies were decided by two review authors in accordance with CONSORT guidelines. Each study was assessed using the evaluation method described in the Cochrane Handbook for Systematic Reviews. Among the 30 studies included in the review, marked degree of relapse in the mandible was noted from 3 months - 1 year postoperatively in 8 studies, 5 studies reported both TMD prevalence and relapse, whereas only 4 studies reported TMD disorder alone. Conclusion: Complications of relapse and TMD are associated with bimaxillary orthognathic surgery procedures. More RCTs and CCTs are needed in this regard to get better quality evidence. This review was registered with PROSPERO: CRD42020211342.